Photosensitizer effects on cancerous cells: A combined study using synchrotron infrared and fluorescence microscopies - Chio-Srichan, Sirinart; Réfrégiers, Matthieu; Jamme, Frédéric; Kascakova, Slavka; Rouam, Valérie; Dumas, Paul (Biochimica et biophysica acta, 2008)
Hypocrellin A (HA), a lipid-soluble peryloquinone derivative, isolated from natural fungus sacs of Hypocrella bambusae, has been reported to be a highly potential photosensitizer in photodynamic therapy (PDT). It has been studied increasingly because of its anticancer activities when irradiated with light. We have studied the interaction mechanisms of HA with HeLa cells as a function of incubation time. Fluorescence microscopy confirmed that HA localisation is limited in the cytoplasm before eventually concentrating in clusters around the nucleus. The IR spectra of HA-treated, PDT-treated and control HeLa cells were recorded at the ESRF Infrared beamline (ID21). Principal component analysis has been used to assess the IR spectral changes between the various HeLa cells spectral data sets (The Unscrambler software, CAMO). PCA revealed that there is a frequency shift of protein amide I and amide II vibrational bands, indicating changes in the protein secondary structures of the HA-treated and PDT-treated cancer cells compared to the control cells. In addition, the relative DNA intensity in HA-treated cells decreases gradually along the incubation time. The use of synchrotron infrared microscopy is shown to be of paramount importance for targeting specifically the biochemical modification induced in the cell nucleus.